A educação/qualificação dos trabalhadores do campo e da cidade na lógica do capital agroindustrial, na cidade de Xaxim (SC) - Skrzypczak, Valdir (2013)
The western region of Santa Catarina is based in the dependence of large economic agro-industrial groups, as BRF, Aurora and Diplomata Industrial and Commercial LTD, which dominate the sector of poultry/pork and its derivatives. In the dialectical relation between the countryside, the city and the agroindustry, the workers have been often qualified/disqualified to take care of the production s interest and the capital s reproduction, imposed by the agro-industrial complex which tries to meet the international market s demands. When the workers qualify/disqualify, they live a contradictory process and a confrontation in the social relations of the production (KUENZER, 2011). When the capital requires more education of the proletarian, it simplifies the activities in the industry, developing the capitalist pedagogy of the skills and competencies, because it expropriates the knowledge in the work relations and internalizes the estranged productions forms. So the worker tries to enlarge the formal schooling, however he/she continues in the employed conditions of the agroindustry, which often tries to capture the subjectivity for the forms consensus of the capitalist production, involving the proletarian in the fabric of the control and mastery s relations. The study s area comprises the municipality of Xaxim, in the Western Catarinense, characterized by the presence of large agro-industrial groups, besides of a significant trade and service s sector. The period to be searched involves the decades from 1960 to 2010, characterized by deep transformations in the labor s world.